Effect of preoperative cancer treatment on epidermal growth factor receptor (EGFR) receptor expression level in ABY-029 guided sarcoma surgery - Xu, Xiaochun (Proc SPIE Int Soc Opt Eng, 2020)
Surgical excision via wide local excision (WLE) of the primary sarcoma tumor is a mainstay of treatment due to the limited effectiveness of chemotherapy and radiation. Even with attempts at WLE, 22–34% of the patient will be diagnosed with a positive margin by the pathologist, necessitating additional radiation or surgery. Recent studies have demonstrated reduced local recurrence when using fluorescence-guided surgery (FGS) to detect residual sarcoma following attempted WLE. ABY-029 is an anti-EGFR Affibody® molecule labeled with IRDye800CW that is currently under Phase 0 human trial for FGS. To date, several studies have been performed to evaluate ABY-029 signal intensity in untreated human sarcoma xenografts; however, many patients undergoing cancer surgery have received pre-operative radiation and/or chemotherapy, which can affect tissue properties and tumor molecule expression level. Determining the effects of radiation and chemotherapy exposure on fluorophore binding in sarcomas may influence best practices in implementing FGS for sarcoma. In this project, fluorophore signal intensities in tumor and surrounding tissue were measured and compared to the receptor concentration determined by immunohistochemistry. Here, we report the result for one EGFR positive synovial sarcoma cell lines, SW982. Four groups of human dose equivalent therapies – control, radiation, chemotherapy (Doxorubicin) and radiation followed by chemotherapy – were given to the tumor-bearing mice. The difference between groups can be used to determine the effects of preoperative sarcoma therapies on EGFR expression, ABY-029 uptake, and optical properties of tissues.